The point is to change the world : selected writings of Andaiye - Andaiye (Black critique., 2020)
"Radical activist, thinker, and comrade of Walter Rodney, Andaiye was one of the Caribbean's most important political voices. For the first time, her writings are published in one collection. Through essays, letters, and journal entries, Andaiye's thinking on the intersections of gender, race, class, and power are powerfully articulated, Caribbean histories emerge, and stories from a life lived at the barricades are revealed. We learn about the early years of the Working People's Alliance, the meaning and impact of the murder of Walter Rodney and the fall of the Grenada Revolution. Throughout, we bear witness to Andaiye's acute understanding of politics rooted in communities and the daily lives of so-called ordinary people. Featuring forewords by Clem Seecharan and Robin DG Kelley, these texts will become vital tools in our own struggles to 'overcome the power relations that are embedded in every unequal facet of our lives.'"--